2004
DOI: 10.1037/1040-3590.16.4.391
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Factor Structure of the Questionnaire on Smoking Urges.

Abstract: This study assessed the factor structure of the Questionnaire on Smoking Urges (QSU), a commonly used assessment of cravings for cigarettes, with a sample of smokers presenting for treatment in a smoking cessation trial. On the basis of previous research, three confirmatory factor analytic models were tested. Model 1 hypothesized a 26-item, 2-factor model using the items reported in the original QSU analysis by S. T. Tiffany and D. J. . Model 2 hypothesized a 12-item, 2-factor model comprised of the 6 most rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 22 publications
(67 reference statements)
2
19
1
Order By: Relevance
“…However, when subjected to confirmatory factor analysis, which allows for a more stringent analysis of the data, the evidence presented in the present study revealed that the data was best explained by a shortened form of the QSU-Brief. These results echo the findings of both Kozlowski et al (1996) and Toll et al (2004), in which the initial factor solution of the 32-item QSU presented by Tiffany and Drobes (1991) was not validated using confirmatory factor analysis. Instead, a model that included a shortened form of the QSU using only the most robust items from the initial factor analysis was found to fit the data best.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…However, when subjected to confirmatory factor analysis, which allows for a more stringent analysis of the data, the evidence presented in the present study revealed that the data was best explained by a shortened form of the QSU-Brief. These results echo the findings of both Kozlowski et al (1996) and Toll et al (2004), in which the initial factor solution of the 32-item QSU presented by Tiffany and Drobes (1991) was not validated using confirmatory factor analysis. Instead, a model that included a shortened form of the QSU using only the most robust items from the initial factor analysis was found to fit the data best.…”
Section: Discussionsupporting
confidence: 71%
“…Taken together with the results of Kozlowski et al (1996) and Toll et al (2004), these findings provide evidence that only the most robust items from the QSU and QSU-Brief are amenable to confirmatory factor analysis.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The following measures were administered at baseline immediately prior to the smoking lapse task: the Wisconsin Smoking Withdrawal Scale measured nicotine withdrawal symptoms (WSWS; Welsch et al, 1999), and the Questionnaire of Smoking Urges-Brief (QSU-Brief) measured urge to smoke and craving (Cox et al, 2001;Toll et al, 2004;Toll et al, 2006). The two factors of the QSUBrief, which capture craving for the positive effects of smoking and craving to relieve the discomfort of nicotine withdrawal (Cox et al, 2001), were analyzed.…”
Section: Proximal Measuresmentioning
confidence: 99%